(untitled) - TEGUH LESMANA, JOHAN (Language Horizon: Journal of Language Studies, 2014)
Child Abuse as Experienced by Sasha in Jennifer Egan’s A Visit from the Goon Squad Johan Teguh Lesmana English Literature Faculty of Languages and Arts State University of Surabaya joehan@outlook.com Drs. Much. Khoiri, M.Si. English Department Faculty of Languages and Arts State University of Surabaya much_choiri@yahoo.com Abstrak Cinta adalah salah satu kebutuhan dasar bagi anak-anak, akan tetapi banyak orang tua gagal untuk menyediakannya. Kegagalan orang tua dalam memenuhi kebutuhan emosional anak-anak mereka mengindikasikan salah satu bentuk kekerasan pada anak, pengabaian emosional. Terlepas dari jenis kekerasan pada anak, dampaknya adalah luka emosional serius dan juga meninggalkan bekas luka yang dalam dan abadi. Kekerasan yang dialami Sasha membawa dampak yang sangat besar terhadap watak dan tingkah lakunya di kemudian hari. Sejalan dengan hal tersebut, tujuan studi ini adalah untuk menggambarkan kekerasan pada anak yang dialami oleh Sasha, dan untuk mengungkapkan dampak kekerasan pada anak terhadap kepribadian Sasha. Studi ini menggunakan teori milik Sigmund Freud mengenai kepribadian sebagai landasan analisis. Berdasarkan hasil analisis, studi ini menunjukkan bahwa kekerasan pada anak dilakukan oleh orang tua Sasha dengan gagal menyediakan cinta atau kasih sayang yang cukup kepada Sasha dan memperlihatkan kekerasan akut pada pasangan atau kekerasan dalam rumah tangga secara langsung. Hasil studi ini juga menunjukkan bahwa kekerasan pada anak seperti yang dialami oleh Sasha membawa banyak dampak terhadap kepribadian Sasha. Dampak-dampak tersebut adalah halusinasi penglihatan, penyangkalan terhadap kenangan masa lalu, kesulitan sosial, pelarian diri, perilaku menyakiti diri sendiri, gangguan pengendalian hasrat, merokok dan penyalahgunaan obat, perilaku kasar, dan perilaku seksual yang menyimpang. Kata Kunci: kekerasan pada anak, pengabaian, kasih sayang, tingkah laku, watak. Abstract Love is one of the basic needs for children, but many parents fail to provide it. Parents’ failure to provide emotional needs for their children indicates a form of child abuse, emotional neglect. Regardless of the type of child abuse, the result is serious emotional harm and also leaves deep, lasting scars. Sasha’s child abuse bring enormous effects on her character and behavior later on her stage of life. In line with that, the purposes of this study are to depict the child abuse as experienced by Sasha, and to reveal the impacts of Sasha’s child abuse on her personality. This study uses Sigmund Freud’s theory of personality as the base for analysis. Based on the analysis, this study shows that child abuse is depicted by Sasha’s parents by failing to provide adequate love or affection to Sasha, and showing chronic spouse abuse or domestic violence. The result of this study shows that child abuse as experienced by Sasha brings changes on Sasha’s personality. They are illusion, denial of past memories, social difficulties, runaway, self-abusive behavior, impulse control disorder, smoking and drug abuse, rude behavior, and sexual misbehavior. Keywords: child abuse, neglect, affection, behavior, character. INTRODUCTION As the winner of Pulitzer Prize for Fiction in 2011, A Visit from the Goon Squad is an interesting novel to be discussed as it tells about psychology side of human’s life. The book zooms around in time and defies linearity so completely, but because it addresses some of life’s big questions, it is philosophically exciting. The characters are all dealing with the passage of time and the effects it has on their lives, beliefs, and relationships. Each chapter is told from a different character’s point of view, though each one recurs earlier or later in the book as a supporting cast member. A Visit from the Goon Squad is Jennifer Egan’s current masterpiece. She has won multiple awards for all her literature works. In A Visit from the Goon Squad, she depicts time as sinister and merciless factor in each character’s life. She exposes how each character fights against time in a unique and complicated way. Ultimately, as the main core, she brings music and love into the journey of time. On the beginning of the story, Sasha appears in her mid-thirties, on her therapist's couch in New York City, confronting her long-standing compulsion to steal. Later on, the story reveals the genesis of her chaos as the child of a violent marriage where she lacks of her parents’ love, then as a runaway living in Naples, then as a college student trying to aver the suicidal impulses of her best friend. Sasha continues to have conflicts with herself throughout the book, such as her desire to steal vs. her desire to change. Sasha's life seems to be in disorder and she has trouble finding friends or success until the end of the book. Those all are derived from one thing, love. Love is one of the basic needs for children. Parents should give their love and attention to their children, because it can help the children grow their personality in a good way. Children tend to do what their parents do. It means that if the parents do something good to their children, the children will do the same to themselves and people around them, and vice versa. Any act of failure to provide for a child’s basic needs, can be called as child abuse or neglect, and it will greatly affects his/her personality in the future. Child abuse and neglect is any recent act or failure to act on the part of a parent or care-taker which results in death, serious physical or emotional harm, sexual abuse or exploitation (Shannon, 2009: 3). Child abuse and neglect can have consequences for children, families, and society that last lifetimes, if not generations. Child abuse is more than bruises and broken bones. Ignoring children’s needs, putting them in unsupervised, dangerous situations, or making a child feel worthless or stupid are also child abuse. Regardless of the type of child abuse, the result is serious emotional harm and also leaves deep, lasting scars. The earlier abused children get help, the greater chance they have to heal and break the cycle. Sasha’s chaos that happened since her early age; lacking of love from her parents and seeing her parents fight each other, is an act of child abuse and neglect. An individual is more desperate during tough times and have a tendency to be impulsive. As Sasha afterward knows that she is the child of a violent marriage, it makes Sasha feels guilty, fearful, dishonest, insecure, vulnerable, and trapped. As the effect of this chaos that happened since her early age, it leads her to some deviate behaviors and personalities later on her stage of life. The way her parents treat her (abuse, neglect, and violence) creates an unconscious thought on her mind, that she deserves it. It is like a time bomb which will eventually explode later on when she cannot bear it anymore. It makes Sasha as a low self-esteem girl who has no brighter future, but darker. As long as she tries to remember her traumatic past events, she gets nothing but painful memories. It sets some long lasting deviate effects on Sasha’s character. Sasha has lived a life where she went from being a runaway in a foreign country who had battled with theft urges to a prostitute and other emotional destabilizing factors. This is represented by the fact that she grew up in a very violent home. The aspects of the things that she did all her life were a representation of what she had witnessed while growing up. In short, one’s youth is responsible for shaping his or her adult behaviors. Discussing and analyzing about character or human, it cannot be separated from personality terms. Sigmund Freud emphasizes how early stage of childhood is important part to create someone’s adulthood personality and behavior. He says that part of our personality is formed on the basis of the unique relationships we have as children with various people and objects. Accordingly we develop a personal set of character attributes, a consistent pattern of behavior that defines each of us as an individual (Shannon, 2009: 64). Nonetheless, based on facts lay on the background of the study above, then the problems are emerged and divided into two: (1) how is child abuse depicted in Jennifer Egan’s A Visit from the Goon Squad?; and (2) what is the impact of child abuse on Sasha’s personality in Jennifer Egan’s A Visit from the Goon Squad. As referred to the background and statement of the problems above, the objectives of the study are devoted to know two purposes as results of analyzing the problems: (1) to depict child abuse in Jennifer Egan’s A Visit from the Goon Squad; and (2) to reveal the impact of child abuse on Sasha’s personality in Jennifer Egan’s A Visit from the Goon Squad. In accordance, it is expected that this study can give both theoretical and practical significance. In theoretical significance, Jennifer Egan’s A Visit from the Goon Squad contains issues regarding child abuse and its impact on personality. Therefore, this study is hoped can obtain positive contribution towards the development of literary theory, which studies literature and society under the concepts of child abuse and theory of personality. Additionally, in practical significance, this study is obtained can contribute to the practice of analyzing literary works by applying proper literary concept and theory. Hopefully, to whom this study may concern, it can be utilized as reference. Furthermore, this study expectantly can assist the institution to provide rich collection of research references. RESEARCH METHOD This study takes the data source from a novel entitled A Visit from the Goon Squad written by Jennifer Egan, published in London by Corsair, with ISBN 978-1-84901-991-0 and ISBN 978-1-78033-096-9 in 2011. To collect the data, the first step is doing close reading the novel entirely. It is done over and over in order to be able to catch and understand the core story—intrinsically and extrinsically—of the novel. Besides, it also aims to support in collecting and analyzing the statement of the problems later on. Secondly, it comes to the step of collecting data. At this point, the data is collected through noting the narration and characters’ dialogue and action in the novel, which reflects the idea of child abuse experienced by Sasha and the impact of child abuse on Sasha’s personality in the form of quotation. Thirdly, it then comes to the step of classifying data. The classification of the collected data is divided into two parts—the data which reflects the case of child abuse, and the impact of child abuse on Sasha’s personality. Last but not least, it reaches the final process of collecting data, which is placing the classified data into the table. It is done to simplify in reading the data for the purpose of doing analysis. Henceforth, in analyzing literary works, Wellek and Warren explain that there are two approaches, intrinsic—encompasses literary work of art, euphony, rhythm, meter, style, stylistic, image, metaphor, symbol, myth, the nature and modes of narrative fiction, literary genres, evaluation, literary history—and extrinsic—encompasses biography, psychology, society, ideas, and the other arts (Wellek & Warren, 1949: 63—282). As a result, since it is clearly shown that Jennifer Egan’s A Visit from the Goon Squad describes Sasha and society surrounds her, it will focus on analyzing the issues upon child abuse and its impact with touching upon personality. Therefore, it is maintained by using extrinsic approach. Nevertheless, the most important thing to analyze a literary work is method and technique. A method is always needed as a tool while technique is the way a tool (method) is used to solve the existed problems (Ratna, 2004: 34—37). Therefore, based upon the statement of the problems above, this study will be analyzed by using descriptive analysis method. This method, Ratna explains further, is used to analyze a problem by describing the facts that contained in the object of the study and then analyzing it with the specific aim to give best explanation and understanding (Ratna, 2004: 53). To simplify the analysis of this study, there are two important steps needed to be done. The first is describing the facts. At this point, the facts are the data in the novel which supports the study or the statement of the problems. It is done by describing the collected and classified data based on the subject of this study—child abuse as experienced by Sasha. The description will touch upon mentioning the detail of the subject, the form of child abuse and the impact of child abuse. Last but not least, the second is doing analysis towards the described data. It will dig the information beyond the data deeper by explaining it thoroughly. It is taken from the data in the novel first and, then, it will be analyzed by based on the thought of the researcher. At this point, to make best explanation and understanding of the study, Shannon’s child abuse and Freud’s personality are included. CHILD ABUSE Maltreatment of children and adolescents occurs in all races, economic levels, religions, family structures, and communities. The national Administration on Children, Youth, and Families states that abuse and neglect can have consequences for children, families, and society that last lifetimes, if not generations (Shannon, 2009: xi). Child abuse is socially defined constructs. It is a product of a particular culture and context, and is not absolute unchanging phenomena. Corby states that what is considered to be abusive or neglectful in a particular society alters over time (Corby, 2006: 79). Corby adds further that place is another factor, what is viewed as abusive in one society today is not necessarily seen as such in another (Corby, 2006: 80). Another general issue relates to the formal definitions of child abuse. There are a bewildering number of such definitions emanating from a wide range of sources. It is important to know who the definers are, and what are their aims, goals, and interests. Robin E. Clark et al., state that child abuse and neglect is a general term that covers a wide range of acts of commission and omission, either carried out by a child’s caretaker or allowed to happen, that result in a range of injuries ranging from death, to serious disabling injury, to emotional distress, to malnutrition and illness (Clark et al., 2007: xiii). In the other hand, as cited by Shannon on his book Child Abuse Sourcebook (2009: 3), The Federal Child Abuse Prevention and Treatment Act (CAPTA) as amended by the Keeping Children and Families Safe Act of 2003, defines child abuse and neglect as, at minimum: • Any recent act or failure to act on the part of a parent or care-taker which results in death, serious physical or emotional harm, sexual abuse or exploitation; or • An act or failure to act which presents an imminent risk of serious harm. Child abuse is more than bruises and broken bones. Ignoring children’s needs, putting them in unsupervised, dangerous situations, or making a child feel worthless or stupid are also child abuse. Regardless of the type of child abuse, the result is serious emotional harm and also leaves deep, lasting scars. The earlier abused children get help, the greater chance they have to heal and break the cycle—rather than perpetuate it. TYPES OF CHILD ABUSE In general, there are numerous kinds of child abuse, but the fundamental element that bonds them together is the same, the emotional effect on the child. Children basic needs are certainty, structure, clear boundaries, and safety. Abused children cannot predict how their parents will act. Their world is an unpredictable, scary, and frightening place with no rules. Whether the abuse is a slap, a harsh comment, stony silence, or not knowing if there will be dinner on the table tonight, the end result is a child that feel unsafe, frightened, uncared for, and alone. Child abuse can take many and varied forms. Shannon (2009: 4) categorizes it into 4 major types; Physical Abuse, Sexual Abuse, Emotional Abuse, and Neglect. They are followed by a wide variety of other more specific abuses. Although any of the forms of child abuse may be found separately, they often occur in combination. Shannon defines physical abuse as non-accidental physical injury (ranging from minor bruises to severe fractures or death) as a result of punching, beating, kicking, biting, shaking, throwing, stabbing, choking, hitting (with a hand, stick, strap, or other object), burning, or otherwise harming a child, that is inflicted by a parent, caregiver, or other person who has responsibility for the child. Such injury is considered abuse regardless of whether the caregiver intended to hurt the child. Physical discipline, such as spanking or paddling, is not considered abuse as long as it is reasonable and causes no bodily injury to the child (Shannon, 2009: 4). Child physical abuse refers to a situation in which a child suffers, or is likely to suffer, significant harm from an injury inflicted by the child’s parent or caregiver. The injury may be inflicted intentionally or may be the inadvertent result of physical punishment or physically aggressive treatment of a child (Shannon, 2009: 133). Physical abuse may lead to bruises, cuts, welts, burns, fractures, internal injuries, or poisoning. In the most extreme cases, physical abuse results in the death of a child. Physical abuse of children is usually regarded as a criminal offense (Shannon, 2009: 133-4). Physical abuse sometimes linked with physical punishment. Physical abuse is an injury resulting from physical aggression. Physical punishment is the use of physical force with the intent of inflicting bodily pain, but not injury, for the purpose of correction or control. Generally, physical punishment can easily get out of control and become physical abuse. The level of punishment which can be inflicted on a child is subject to legal regulation. Physical punishment of children for the purpose of discipline, by parents or caregivers, is permitted by law provided it falls within the bounds of reasonable chastisement, is seen as moderate, and is administered for the purpose of correcting behavior. Reasonable chastisement is a term which is difficult to define precisely. Reasonableness is a flexible concept which involves taking all relevant factors into account. Whether chastisement is reasonable, according to the law will depend on age of the child, stature of the child, health and intellectual capacity of the child, method of and reason for, and the harm caused to the child (Shannon, 2009: 136-7). Child physical abuse is often the inadvertent result of physical punishment administered by an angry, frustrated parent. Sometimes, however, physical discipline is intended to harm the child. Physical punishment which results, intentionally or unintentionally, in injury or tissue damage to the child or young person is physical abuse and may become the grounds for a charge of assault. (Shannon, 2009: 137). Sexual abuse is any sexual act includes activities by a parent or caregiver such as fondling a child’s genitals, penetration, incest, rape, sodomy, indecent exposure, and exploitation through prostitution or the production of pornographic materials (Shannon, 2009: 5). Sexual abuse between children is often defined as when there is a significant age difference (usually three or more years) between the children, or if the children are very different developmentally or size-wise. Shannon adds that sexual abuse does not have to involve penetration, force, pain, or even touching. If an adult engages in any sexual behavior (looking, showing, or touching) with a child to meet the adult’s interest or sexual needs, it is sexual abuse (Shannon, 2009: 206-7). People who may sexually abuse children are fathers, mothers, step-parents, grandparents, uncles, aunts, and cousins. They are neighbors, baby sitters, religious leaders, teachers, coaches, and strangers. They come from all classes, racial and religious backgrounds, and may be homosexual or heterosexual. Most of those we know about who sexually abuse children are men, but some are women (Shannon, 2009: 207). Some people who abuse children have adult sexual relationships and are not solely, or even mainly, sexually interested in children. More than a third of those who engage in sexual activity with children are under the age of 18 themselves. In many of these instances, the abusive child may not understand that his or her sexual actions toward another child are harmful (Shannon, 2009: 208). Some people who sexually abuse children were victims of abuse or neglect as children. And having been abused as a child does heighten the risk for becoming someone who sexually abuses children. It’s not an excuse, just a fact. But many childhood experiences besides sexual abuse are associated with sexually harmful behavior in youth, including exposure to violence, lack of emotional connection early in life, and physical abuse. Acknowledging and addressing the distress these children have already faced is a good way to begin ending this abusive cycle. Experts and parents agree that with specialized treatment these children can heal. Shannon defines emotional abuse as a pattern of behavior by parents or caregivers that can seriously interfere with a child’s cognitive, emotional, psycho-logical, or social development (2009: 169). Emotional abuse is often difficult to prove and, therefore, child protective services may not be able to intervene without evidence of harm or mental injury to the child. Emotional abuse is almost always present when other forms are identified. Emotional abuse of a child can include the following: ignoring, rejecting, isolating, exploiting or corrupting, verbally assaulting, and terrorizing. While the definition of emotional abuse is often complex and imprecise, professionals agree that, for most parents, occasional negative attitudes or actions are not considered emotional abuse. Even the best of parents have occasions when they have momentarily lost control and said hurtful things to their children, failed to give them the attention they wanted, or unintentionally scared them. Emotional abuse can, and does, happen in all types of families, regardless of their background. Most parents want the best for their children. However, some parents may emotionally and psychologically harm their children because of stress, poor parenting skills, social isolation, lack of available resources, or inappropriate expectations of their children. They may emotionally abuse their children because the parents or caregivers were emotionally abused themselves as children. Shannon states that children who are constantly ignored, shamed, terrorized, or humiliated suffer at least as much, if not more, than if they are physically assaulted (2009: 171). Although the visible signs of emotional abuse in children can be difficult to detect, the hidden scars of this type of abuse manifest in numerous behavioral ways, including insecurity, poor self-esteem, destructive behavior, angry acts (such as fire setting and animal cruelty), withdrawal, poor development of basic skills, alcohol or drug abuse, suicide, difficulty forming relationships, and unstable job histories. Emotionally abused children often grow up thinking that they are deficient in some way. A continuing tragedy of emotional abuse is that when these children become parents they may continue the cycle with their own children. Neglect is the failure of a parent, guardian, or other caregiver to provide for a child’s basic needs (Shannon, 2009: 4). While neglect may be harder to define or to detect than other forms of child maltreatment, there are common categories of neglect: physical neglect, emotional neglect, medical neglect, educational neglect, and inadequate supervision. Emotional neglect is the most common neglect. It is inattention to a child’s emotional needs, failure to provide psychological care, or permitting the child to use alcohol or other drugs. Emotional neglect is more difficult to assess than other types of neglect, but is thought to have more severe and long lasting consequences than physical neglect. It often occurs with other forms of neglect or abuse, which may be easier to identify, and includes the following: inadequate nurturing or love, chronic spouse abuse, maladaptive behavior, and isolation. Shannon emphases that the impact of neglect on a child may not be apparent at an early stage except in the most extreme cases (2009: 59). However, the effects of neglect are harmful and possibly long-lasting for the victims. Its impact can become more severe as a child grows older and can encompass multiple areas, such as health and physical development, intellectual and cognitive development, emotional and psychological development, and social and behavioral development. Although there are four categories of neglect’s effects on an individual, they often are related. For example, if a child experiences neglect that leads to a delayed development of the brain, this may lead to cognitive delays or psychological problems, which may manifest as social and behavioral problems. Because neglected children often experience multiple consequences that may be the result of neglect and related circumstances in their lives, it may be difficult to determine if the impact is related specifically to the neglect, is caused by another factor, or arises from a combination of factors (Shannon, 2009: 59). All types of neglect, and emotional neglect in particular, can have serious psychosocial and emotional consequences for children. Some of the short-term emotional impacts of neglect, such as fear, isolation, and an inability to trust, can lead to lifelong emotional and psychological problems, such as low self-esteem (Shannon, 2009: 65). Neglected children, even when older, may display a variety of emotional, psychosocial, and behavioral problems which may vary depending on the age of the child. Some of the scariest are: displaying an inability to control emotions or impulses (usually characterized by frequent outbursts), displaying self-abusive behavior (for example, suicide attempts or cutting themselves), exhibiting panic or dissociative disorders (attention-deficit or hyperactivity disorder, or post-traumatic stress disorder), suffering from depression, anxiety, or low self-esteem, and exhibiting juvenile delinquent behavior. IMPACTS OF CHILD ABUSE The impact of child abuse vary widely and are affected by a combination of factors, such as age, type of abuse, the frequency, and the relationship between the victim and his or her abuser. Although it seems as if decisions and events made during a person’s childhood are totally irrelevant towards the rest of his/her life, these factors make a tremendous impact on the type of adult a person becomes. For example, it is commonly known that most children who had abusive parents have grown up to be just the same. If a child had very loving and caring parents, chances are the child will grow to be very loving parents towards his/her children. The immediate physical effects of abuse or neglect can be relatively minor (bruises or cuts) or severe (broken bones, hemorrhage, or even death). In some cases the physical effects are temporary; however, the pain and suffering they cause a child should not be discounted (Shannon, 2009: 86). Meanwhile, the long-term impact of child abuse and neglect on physical health is just beginning to be explored. The immediate emotional effects of abuse and neglect—isolation, fear, and an inability to trust—can translate into lifelong impacts, including low self-esteem, depression, and relationship difficulties. Researchers (Shannon, 2009: 87) have identified links between child abuse and neglect and the following: difficulties during infancy, poor mental and emotional health, cognitive difficulties, and social difficulties. Not all victims of child abuse and neglect will experience behavioral consequences. However, behavioral problems appear to be more likely among this group, even at a young age (Shannon, 2009: 88). Later in life, child abuse and neglect appear to make the following more likely: difficulties during adolescence, alcohol and drug abuse, abusive behavior, and juvenile delinquency. Shannon adds further, while child abuse and neglect almost always occur within the family, the impact does not end there. Society as a whole pays a price for child abuse and neglect, in terms of both direct and indirect costs (2009: 89). Direct costs include those associated with maintaining a child welfare system, while indirect costs represent the long-term economic impacts of child abuse and neglect. PERSONALITY Adams, on Schultz’s Theories of Personality suggested that we can get a good idea of its meaning if we examine our intentions whenever we use the word I (Schultz, 2009: 8). When you say I, you are, in effect, summing up everything about yourself—your likes and dislikes, fears and virtues, strengths and weaknesses, etc. The word I is what defines you as an individual, separate from all others. Schultz (2009: 8) explains that personality derives from the Latin word persona, which refers to a mask used by actors in a play. It is easy to see how persona came to refer to outward appearance, the public face we display to the people around us. Based on its derivation, we might conclude that personality refers to our external and visible characteristics, those aspects of us that other people can see. Our personality would then be defined in terms of the impression we make on others—that is, what we appear to be. In short, our personality may be the mask we wear when we face the outside world. Personality refers to the characteristics patterns of behavior and ways of thinking that determine a person’s adjustment to his environment. The personality of somebody has built from the experiences that they got from the social surrounding and also the genetic factor gives the background of someone’s personality. By showing this theory, it can be concluded that the development of somebody’s personality depends on the experience and the condition surrounding that, leads to the finding of personality. Instincts are the basic elements of the personality, the motivating forces that drive behavior and determine its direction. Freud’s German term for this concept is Trieb, which is best translated as a driving force or impulse (Schultz, 2009: 54). Instincts are a form of energy—transformed physiological energy—that connects the body’s needs with mind’s wishes. The stimuli (hunger or thirst, for example) for instincts are internal. When a need such as hunger is aroused in the body, it generates a condition of physiological excitation of energy. The mind transforms this bodily energy into a wish. It is this wish—the mental representation of the physiological need—that is the instinct or driving force that motivates the person to behave in a way that satisfies the need. For example, a hungry person will act to satisfy his or her need by looking for food. The instinct is not the bodily state; rather, it is the bodily need transformed into a mental state, a wish (Schultz, 2009: 54). When the body is in a state of need, the person experiences a feeling of tension or pressure. Freud states that the aim of an instinct is to satisfy the need and thereby reduce the tension (Schultz, 2009: 54). Freud believed that we always experience a certain amount of instinctual tension and that we must continually act to reduce it. It is not possible to escape the pressure of our physiological needs as we might escape some annoying stimulus in our external environment. This means that instincts are always influencing our behavior, in a cycle of need leading to reduction of need. As stated by Freud, people may take different paths to satisfy their needs (Schultz, 2009: 55). Freud thought that psychic energy could be displaced to substitute objects, and this displacement was of primary importance in determining an individual’s personality. Although the instincts are the exclusive source of energy for human behavior, the resulting energy can be invested in a variety of activities. This helps explain the diversity we see in human behavior. All the interests, preferences, and attitudes we display as adults were believed by Freud to be displacements of energy from the original objects that satisfied the instinctual needs. Freud’s personality theory is at least partly autobiographical in that he based some of his major concepts on his childhood experiences. Freud’s original conception divided personality into three levels: the conscious, the preconscious, and the unconscious. Freud later revised this notion of three levels of personality and introduced three basic structures in the anatomy of the personality: the id, the ego, and the superego. The id corresponds to Freud’s earlier notion of the unconscious (although the ego and superego have unconscious aspect as well). Freud emphasizes that the id is the reservoir for the instincts and libido (the psychic energy manifested by the instincts) (Schultz, 2009: 57). The id is a powerful structure of the personality because it supplies all the energy for the other two components. Because the id is the reservoir of the instincts, it is vitally and directly related to the satisfaction of bodily needs. As noted earlier, tension is produced when the body is in a state of need, and the person acts to reduce this tension by satisfying the need. The id operates in accordance with what Freud called the pleasure principle; the principle by which the id functions to avoid pain and maximize pleasure (Schultz, 2009: 57). The id strives for immediate satisfaction of its needs and does not tolerate delay or postponement of satisfaction for any reason. It knows only instant gratification; it drives us to want what we want when we want it, without regard for what anyone else wants. The id is a selfish, pleasure-seeking structure, primitive, amoral, insistent, and rash. Most children learn that they cannot take food from other people unless they are willing to face the consequences. The growing child is taught to deal intelligently and rationally with the outside world and to develop the powers of perception, recognition, judgment, and memory—the powers adults use to satisfy their needs. Freud called these abilities as secondary-process thought (Schultz, 2009: 58). We can sum up these characteristics as reason or rationality, and they are contained in Freud’s second structure of personality, the ego, which is the rational master of the personality (Schultz, 2009: 58). Its purpose is not to thwart the impulses of the id but to help the id obtain the tension reduction it craves. Because it is aware of reality, the ego decides when and how the id instincts can best be satisfied. It determines appropriate and socially acceptable times, places, and objects that will satisfy the id impulses. The ego does not prevent id satisfaction. Rather, it tries to postpone, delay, or redirect it in terms of the demands of reality. It perceives and manipulates the environment in a practical and realistic manner and so is said to operate in accordance with the reality principle (The reality principle stands in opposition to the pleasure principle, by which the id operates). The ego thus exerts control over the id impulses. Freud compared the relationship of the ego and the id to that of a rider on a horse. The raw, brute power of the horse must be guided, checked, and reined in by the rider; otherwise the horse could bolt and run, throwing the rider to the ground (Schultz, 2009: 58). The id and the ego do not represent Freud’s complete picture of human nature. There is a third set of forces—a powerful and largely unconscious set of dictates or beliefs—that we acquire in childhood: our ideas of right and wrong. In everyday language we call this internal morality a conscience. Freud called it the superego. Freud stated that the basis of this moral side of the personality is usually learned by the age 5 or 6 and consists initially of the rules of conduct set down by our parents (Schultz, 2009: 59). Freud added through praise, punishment, and example, children learn which behaviors their parents consider good or bad. Those behaviors for which children are punished form the conscience, one part of the superego. The second part of the superego is the ego-ideal, which consists of good, or correct, behaviors for which children have been praised (Schultz, 2009: 59). The id and the ego do not represent Freud’s complete picture of human nature. There is a third set of forces—a powerful and largely unconscious set of dictates or beliefs—that we acquire in childhood: our ideas of right and wrong. In everyday language we call this internal morality a conscience. Freud called it the superego. Freud stated that the basis of this moral side of the personality is usually learned by the age 5 or 6 and consists initially of the rules of conduct set down by our parents (Schultz, 2009: 59). Freud added through praise, punishment, and example, children learn which behaviors their parents consider good or bad. Those behaviors for which children are punished form the conscience, one part of the superego. The second part of the superego is the ego-ideal, which consists of good, or correct, behaviors for which children have been praised (Schultz, 2009: 59). In this way, children learn a set of rules that earn acceptance or rejection from their parents. In time, children internalize these teachings, and the rewards and punishments become self-administered. Parental control is replaced by self-control. We come to behave at least in partial conformity with these now largely unconscious moral guidelines. As a result of this internalization, we experience guilt or shame whenever we perform (or even think of performing) some action contrary to this moral code (Schultz, 2009: 59). The superego strives neither for pleasure (as does the id) nor for attainment of realistic goals (as does the ego). It strives solely for moral perfection. The id presses for satisfaction, the ego tries to delay it, and the superego urges morality above all. Like the id, the superego admits no compromise with its demands (Schultz, 2009: 59). Anxiety is not unlike fear, although we may not know what we are frightened of. Freud described anxiety as an objectless fear; a feeling of fear and dread without an obvious cause (Schultz, 2009: 59). Freud made anxiety an important part of his personality theory, asserting that it is fundamental to the development of neurotic and psychotic behavior. Freud suggested that the prototype of all anxiety is the birth trauma (Schultz, 2009: 59). He later explained it in a long explanation (Schultz, 2009: 59-60): The fetus in its mother’s womb is in the most stable and secure of worlds, where every need is satisfied without delay. But at birth, the organism is thrust into a hostile environment. Suddenly, it is required to begin adapting to reality because its instinctual demands may not always be immediately met. The newborn’s nervous system, immature and ill prepared, is bombarded with diverse sensory stimuli. Consequently, the infant engages in massive motor movements, heightened breathing, and increased heart rate. This birth trauma, with its tension and fear that the id instincts won’t be satisfied, is our first experience with anxiety. From it is created the pattern of reactions and feelings that will occur whenever we are exposed to some threat in the future. Freud proposed three types of anxiety: reality anxiety, neurotic anxiety, and moral anxiety (Schultz, 2009: 60). Reality anxiety is a fear of tangible dangers in the real world. Most of us justifiably fear fires, hurricanes, earthquakes, and similar disasters. We run from wild animals, speeding cars, and burning buildings. Reality anxiety serves the positive purpose of guiding our behavior to escape or protect ourselves from actual dangers. Our fear subsides when the threat is no longer present. The other kinds of anxiety, neurotic anxiety and moral anxiety, are more consistently troublesome to our mental health. Neurotic anxiety has its basis in childhood, in a conflict between instinctual gratification and reality. Children are often punished for overtly expressing sexual or aggressive impulses. Therefore, the wish to gratify certain id impulses generates anxiety. This neurotic anxiety is an unconscious fear of being punished for impulsively displaying id-dominated behavior. The conflict becomes one between the id and the ego, and its origin has some basis in reality (Schultz, 2009: 60). Moral anxiety results from a conflict between the id and the superego (Schultz, 2009: 60). In essence, it is a fear of one’s conscience. When you are motivated to express an instinctual impulse that is contrary to your moral code, your superego retaliates by causing you to feel shame or guilt. In everyday terms, you might describe yourself as conscience-stricken. Moral anxiety is a function of how well developed the superego is (Schultz, 2009: 60). Anxiety is a signal that impeding danger, a threat to the ego, must be counteracted or avoided. The ego must reduce the conflict between the demands of the id and strictures of society or the superego. According to Freud, this conflict is ever present because the instincts are always pressing for satisfaction, and the taboos of society are always working to limit such satisfaction (Schultz, 2009: 61). Freud believed that the defenses must, to some extent, always be in operation. All behaviors are motivated by instincts; similarly, all behaviors are defensive in the sense of defending against anxiety. The intensity of the battle within the personality may fluctuate, but it never ceases. Freud postulated several defense mechanisms (Table 2.1) and noted that we rarely use just one; we typically defend ourselves against anxiety by using several at the same time (Schultz, 2009: 61). Although defense mechanism vary in their specifics, they share two characteristics: (1) they are denials or distortions of reality, and, (2) they operate unconsciously (Schultz, 2009: 61). We are unaware of them, which means that on the conscious level we hold distorted or unreal images of our world and ourselves. Freudian defense mechanisms are repression, denial, reaction formation, projection, regression, rationalization, displacement, and sublimation. Freud believed that all behaviors are defensive but that not everyone uses the same defenses in the same way (Schultz, 2009: 64). All of us are driven by the same id impulses, but there is not the same universality in the nature of the ego and superego. Although these structures of the personality perform the same functions for everyone, their content varies from one person to another. They differ because they are formed through experience, and no two people have precisely the same experiences, not even siblings reared in the same house. Thus, part of our personality is formed on the basis of the unique relationships we have as children with various people and objects. We develop a personal set of character attributes, a consistent pattern of behavior that defines each of us as an individual (Schultz, 2009: 64). A person’s unique character type develops in childhood largely from parent-child interactions. The child tries to maximize pleasure by satisfying the id demands, while parents, as representatives of society, try to impose the demands of reality and morality. So important did Freud consider childhood experiences that he said the adult personality was firmly shaped and crystallized by the fifth year of life (Schultz, 2009: 64). Freud perceived that the adult neurosis had been formed in the early years of life. CHILD ABUSE EXPERIENCED BY SASHA A healthy family (where child basic needs are fulfilled, no violence in the family, parents have time to look after their children properly, and parents show good behavior in front of their children) tends to create a good personality and behavior child. In the other hand, a broken family (where child basic needs are not fulfilled, rude behavior parents, parents fight each other in front of their child, and divorced parents) tends to create a bad personality and behavior child. As emphasized by Freud (Schultz, 2009: 64), adult personality is built and firmly shaped by the fifth year of life. One of the most important factors of child basic needs is love or affection. Lack of love or affection could indicate that there is something wrong in the family. Ignoring children’s needs, in this case love or affection, is also an act of child abuse. As stated by Shannon on his book about types of child abuse, there are four main types, physical abuse, emotional abuse, sexual abuse, and neglect (2009: 4). The child abuse happened to Sasha is a form of neglect, emotional neglect. Emotional neglect is a parent’s failure to respond to a child’s emotional needs, including warmth, security, and love. Shannon emphases that the impact of neglect on a child may not be apparent at an early stage except in the most extreme cases (2009: 59). However, the effects of neglect are harmful and possibly long-lasting for the victims. There are two main factors of emotional neglect depicted by Sasha’s parents, they are inadequate love and chronic spouse abuse. The parent-child relationship consists of a combination of behaviors, feelings, and expectations that are unique to a particular parent and a particular child. The parent-child relationship has an important influence on the child’s psychological development. Children who are loved thrive better than those who are not. These children are likely to grow up having the highest level of self-esteem and confidence. Vice versa, inadequate love will create children with the lowest level of self-esteem and confidence. Sasha got her love or affection mostly from her own uncle, Ted. While her parents, Andy and Beth, were busy fighting each other every single day. “When they fought, Ted would take Sasha outside, through the razor-edged grass, to the beach.” (Egan, 2011: 226) Andy and Beth are not a good-typical parents, who raise their child together with full joy and love. They were careless and unaware of their child’s need for affection. Since her early age, Sasha was handed to her uncle every time they fought. As a five years old daughter, Sasha was lovely. She likes to swim. Her uncle would take her outside to the beach every time Andy and Beth fought. Ted would carry her nicely when they went out to the sand that was too hot in the late afternoons for Sasha to walk on without screaming. The development of a child’s behavior is strongly influenced by how well his or her family functions. Ted was pity for Sasha because she had to bear with this kind of parents and live amid so much violence and lack of love from her own parents. Ted wondered what Sasha will become, as she had to bear this since her early age. Sasha had to stand with this condition since her very early age. She more likely to talk with her uncle than her parents. She talked like a normal five years old girl. However Sasha never once talked or asked about whatever was going inside the house. Sasha’s emotional neglect occurred as her parents failed to provide emotional support and adequate love to their daughter. Parent’s love is bigger than uncle’s love, but Beth and Andy failed to provide it. Being in the hardship since her early age, forced Sasha to cope with this situation which will, eventually, affects her psychological development. Ignored or neglected child will often conclude that he or she is bad, unworthy, unlovable, or incompetent. If a parent maltreats the child, the child will thinks he deserves it. When a parent withholds affection and love, the child will interprets himself as unlovable. Therefore the first few years of a child’s life sets the stage for this view of self, and thereafter affects his entire life based on the rejecting, and neglecting behavior of others, not on the truth about who he is. Emotional neglect denies the child the tools needed to cope with stress, and to learn life’s lessons. So a child who is severely neglected may become depressed or develop suicidal, withdrawn, or violent behavior. As he or she gets older, he or she may use drugs and alcohol, or try to run away from the house. When he or she becomes adult, he or she may shows depression, or suicidal behavior. The longer the neglect continues, and the closer the child’s relationship with the neglecter, the more serious the emotional damage will be. Beth and Andy’s marriage was in chaos. They fought day-to-day and forgot to provide emotional support to their only daughter. The worst had come when finally they divorced. “Beth and Andy’s marriage had died spectacularly the summer Ted lived with them on Lake Michigan while managing a construction site two miles farther up the lake.” (Egan, 2011: 225) As parents, Beth and Andy had failed to provide adequate love and emotional support to their daughter, Sasha. Things even went worse when they become single parent. A single parent’s love is not equal to parents’ love. Because she needs both mother and father figure to provide emotional support. Whatever the reason was, divorce only brings more sorrow to Sasha. Sasha was only five years old when Beth and Andy divorced. It was not so long after Ted took Sasha to the beach and trained her to swim. For a five years old girl, this divorce gives nothing but bad reminiscence of her parents. The figure of parents who should give love, attention, and good example, was vanished. As a five years old daughter, Sasha thought that her parents abandoned, neglected, and ignored her again. She worried who will take care of her. She were frightened she will be abandoned by one or both of her parents. This is indirectly a form of emotional neglect. Her parents, for the second time, failed to be a good typical parents who raise their child together with full joy and love, and failed to give a secure feeling condition to Sasha. This wound of reality distortion often creates a significant self-neglect. The child will not care about his or her own physical, emotional, and spiritual health. It is mostly accompanied by self-dislike, self-disgust, or self-hatred. They rise from extreme shame and guilt learned on the very early age – raising a certainty that he or she is worthless and unlovable, and doesn’t deserve to be loved, happy, or healthy. Children who experienced rejection or neglect are more likely to develop antisocial traits as they grow up. Children who are emotionally neglected then grow up to have a particular set of struggles. Because their emotions were not confirmed as children, they may have difficulty knowing and trusting their own emotions as adults. The Father figure has direct impact on the well-being of the children. Fathers who treat the mothers and the children with respect and deal with conflict within the relationship in an adult and appropriate manner are more likely to have, boys who understand how they are to treat women and who are less likely to act in aggressive fashion toward females; girls, who know how they should expect men to treat them and are less likely to become involved in violent relationships. In contrast, fathers or husbands who display anger, show contempt, or who stonewall their wives and children, are more likely to have children who are anxious, withdrawn, or antisocial. The disappearance of her father, gives a big impact on Sasha’s personality and behavior. As a young girl, she learned how to solve a problem in the wrong way. Later on when she was a teenager, she did what her father has done, run away. She run away from her house to Naples when she was seventeen years old. It was her uncle, Ted, who came to Naples to pick her up as requested by her mother, Beth. The exposure of chronic spouse abuse or domestic violence in the family is also indicating emotional neglect. Domestic violence is a pattern of behavior which involves the abuse by one partner against another within family. It is when parents fight in front of the children, or the children hear the fight, and see or notice the scar in their parent’s body. As noted earlier that Andy was a temperamental father and husband, the fights happened almost every day. Their marriage was not run well because of it. When they fought, Ted would take Sasha to the beach, so his niece would not see the fight. However, the scar on her mother’s body could not be covered up anymore, and stood out as the evidence of violence that was happened. “Apart from the marriage itself, the casualties by summer’s end included the majolica plate Ted had given Beth for her birthday; sundry items of damaged furniture; Beth’s left shoulder, which Andy dislocated twice; and her collarbone, which he broke.” (Egan, 2011: 225) Andy was not reluctant to throw anything when he was angry, including the majolica plate which was Ted’s gift for Beth’s birthday. The throws was hitting the furniture in the house and creating a mess of fractions. The more horrible violence was when Andy using physical violence while they fought. When he was angry, he would lose control of himself. He would not hesitate to commit violence and hurt his own wife. Andy has dislocated Beth’s left shoulder twice and broke her collarbone. Those were the evidence on how ruthless Andy to his own wife. The domestic violence that happened was very awful for Sasha, a five years old daughter. It is not the kind of family where happiness and love exist, only sorrow lays down inside the family. The anger and the temper of her father, would become the nightmare on Sasha’s life. She lived amid such violence, and eventually, this experience would be her lifetime guide. It is important to notice that the effects of domestic violence can be overwhelming to experience. Domestic violence can change her worldview and outlook on life. Being in a situation where a person is being controlled or hurt by another can create feelings of hopelessness. For a five years old daughter, it can have a serious impact on the way she thinks and interacts with the world around her. It can also take away her sense of safety and security, which will influence her ability to trust others. The chronic exposure to domestic violence can cause not only immediate physical injury, but also mental shifts that occur as the mind attempts to process trauma or protect the body. Domestic violence affects one’s thoughts, feelings and behaviors and can significantly impact one’s mental stability. Later on, Andy did not only hurt his wife, but also his only daughter, Sasha. When Ted finally found Sasha on Naples, in the evening they had walk until reached a nightclub. At the nightclub, Ted took Sasha’s arm and noticed that there were something wrong on her forearms. At first, Sasha tried to hide the scar and would not let her uncle see it. Then Ted reached her arm by force and it surprised her. Finally she relented and admitted that it was from Los Angeles, when she lived with her parents. Ted realized that her forearms were scarred and scuffed like household furniture. The scar on Sasha’s forearms was the physical indicator on how Andy physically abused her daughter. Physical abuse is a non-accidental physical injury (ranging from minor bruises to severe fractures or death) as a result of punching, kicking, hitting, or otherwise harming a child, which is inflected by a parent or caregiver (Shannon, 2009:4). Physical abuse is often the inadvertent result of physical punishment administered by an angry or frustrated parents. Her scarred and scuffed arms which were still exist until her teenage, may indicate repeated abuse or the use of hard tool to hit. That was why she had lifelong imprint on her arms. Even though the effect of this physical abuse is relatively minor (bruises or scars), however the pain and suffering she endures since her early age should not be discounted. Meanwhile, the long-term impact of her physical abuse and emotional neglect are just beginning to be explored. IMPACTS ON SASHA’S PERSONALITY The personality of somebody is built from the experiences they got from the social surrounding and also the genetic factor gives the background of someone’s personality. Part of our personality is formed on the basis of the unique relationships we have as children with various people and objects. We develop a personal set of character attributes that defines each of us as an individual. A person’s unique character type develops in childhood largely from parent-child interactions. Childhood experiences play a big role in creating someone’s personality. According to Freud, the adult personality was firmly shaped and crystallized by the fifth year of life (Schultz, 2009: 64). In Jennifer Egan’s A Visit from the Goon Squad, Sasha has a terrible childhood life. As a five years old daughter, she was lovely. But her loveless and violent parents made her a misguided child. Her parents were busy fighting without noticing their daughter emotional needs. Meanwhile, her childhood experiences put greatest effect on her personality changes later on her adulthood life. All the violence and sorrow she endured since her early age, is like a bomb that will explode on her adulthood. Young adults who had been abused will suffer both emotionally and psychologically. At least one psychiatric disorder will be displayed by the age 21. These young adults exhibited many mental and emotional problems, including depression, anxiety, eating disorder, suicide attempts. Other psychological conditions related with abuse and neglect include panic disorder, hyperactivity disorder, anger, denial, and post-traumatic stress disorder. Adulthoods’ behavior will reflect what they have been faced during their childhood. For abused child like Sasha, she will have difficulties during her adolescence. She is more likely to experience problems such as juvenile delinquency, drug and alcohol use, and mental health problems. Sasha’s childhood is a terrifying experience for her. Especially the experience with her father who physically abused and neglected her. It is like a repeated nightmare on her life. This traumatic past event can cause her to see unreal things based on her mind. Sasha saw unreal things about her father when she ran away from her house to China, Morocco, before she went to Naples. What she has seen is actually the dark part of her memory about her father. She kept seeing the shadow of her father because she was afraid that her father would find her during her runaway to China, and punish her like he used to do. What happened to Sasha is actually a post-traumatic stress disorder, which is one of the long-term impacts of child abuse and neglect. This mental health condition can be triggered by a terrifying or traumatic event. Some common symptom associated with post-traumatic stress disorder are flashbacks, nightmares, severe anxiety, and thoughts about the event. People who go through traumatic events have difficulty adjusting and coping. The same goes with Sasha. She was haunted by her father’s memory, and it scared her. This kind of fear called neurotic anxiety. Neurotic anxiety has its basis in childhood, in a conflict between instinctual gratification and reality. It is an unconscious fear of being punished. It is the conflict between id and the ego with its origin based on reality. It is normal for abused and neglected children to hide their traumatic past experiences. Later on her life, Sasha does not want to remember everything about her past, because she lives as a different person now. She hide her traumatic past experience by denying its existence. On chapter 12 of Egan’s A Visit from the Goon Squad, a power point-style chapter, Sasha has married Drew Blake, her university boyfriend. She has two children, a son, Lincoln and a daughter, Alison. When her son asked her regarding her reasons for not talking or sharing about her past, she said bluntly that she did not trust her memories. She was trying to hide all the pain and struggles she endured from her son, and especially from herself. Sasha’s denial to her past indicates she does not want anything from her past reappears again on her current life, even just reappears on her mind. Let the bygones be bygones, that was how she wanted to think. However it was also her way to safe her from her anxiety of her terrifying and traumatic past experience. By saying “I don’t trust memories”, she denies the truth that, consciously, she still remember about her past, but her unconsciousness denies it. The way to safe her from her own anxiety is a form of defense mechanism, denial. Denial on defense mechanism is related to repression and involves denying the existence of some external threat or traumatic event that has occurred. It involves the expressing of an id impulse that is the opposite of the one that is truly driving the person. Her defense mechanism, denial, forces her to deny the truth about her past experience, even though her consciousness remember it. She wanted to hide her past life, as she lives a different life as a different person now. She implied clearly that “I never looked back,” she says. (Egan, 2011: 263) She was also used another form of defense mechanism, Repression. To clearly deny her past, she has to deny the person who causes her anxiety, her father. By using repression, she was unconsciously denying the existence of something that causes her anxiety from conscious awareness, i